APPLICATION OF HISTORIC SITES MOSQUE IN INDONESIA USING MACROMEDIA DREAMWEAVER MX 2004 - Muhammad Riefdan; Ire Puspa Wardhani, Skom, MMSI Ire Puspa Wardhani, Skom, MMSI (Jurnal Sistem Informasi, 2007)
In making the application of this website is based on many historical places inIndonesia that are not known to the people, but these places have high historicalvalue, especially if used as a medium for learning and recreation. At this time ofwriting the author would like to introduce these historic places and promotes as onetourist attraction in Indonesia through the media.In scientific writing, the writer gives information about mosques, especially thereligious tourist attraction located in Jakarta, Java, Sumatra, which will featureinformation about the history, facilities and image building that would be presented ina simple website also interesting. Making a web site starts from the navigationstructure, design the page, making page, until a way to upload the website.